Classical Models, Sonata Theory, and the First Movement of Liszt’s Faust Symphony - Howard Cinnamon (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Recent theories of sonata form compensate for a perceived overemphasis on harmonic structure during the latter half of the twentieth century by emphasizing thematic organization as the determining feature of formal function. The present study demonstrates how an analytical method based on earlier practice can be valuable in the analysis of one of Liszt’s most unconventional pieces, the first movement of the Faust Symphony. Initially, it considers “problematic” passages often thought to deviate from earlier conventions, and by offering alternative readings, it shows how they are actually consistent with those earlier practices. Once clarified, the movement’s large-scale tonal structure, and its relationship to thematic material, is compared with earlier, harmonically based models of sonata form (by Kollmann, Galeazzi, and Czerny), in order to demonstrate that the movement adheres to those models in remarkably consistent ways. The study then employs aspects of Hepokoski’s and Darcy’s Sonata Theory to show how its conclusions differ, and how the present methodology might be complementary.